Asupan lemak jenuh dan serat pada remaja obesitas kaitannya dengan sindrom metabolik - Nurmasari Widyastuti; Fillah Fithra Dieny; Deny Yudi Fitranti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: There is an emerging global increase of metabolic syndrome prevalence due to increasing of obesity. Obesity and metabolic syndrome beginning in childhood progressing into adulthood. Dietary saturated fat and fiber intake play a role in etiology in obesity.Objective: This study was to examine the associations between dietary saturated fat intake, fiber intake and components of metabolic syndrome among obese adolescents.Method: A cross-sectional study was conducted to 57 obese students aged 13-15 years old of SMP Nasima and SMP Kesatrian 2 Semarang, based on body mass index for ages. Subjects of this study were collected consecutively. Data were collected through waist circumference and blood pressure measurements, fasting biochemical serum analysis and dietary intake assessment. Rank Spearman and Pearson correlation test was used to examine the associations between of dietary saturated fat and fiber intake to components of metabolic syndrome.Results: There were 46 subjects (80,7 %) had metabolic syndrome and 11 subjects (19,3 %) had the pre-metabolic syndrome. There was no association between dietary saturated fat intake and waist circumference, HDL cholesterol, triglyceride, fasting blood glucose levels and blood pressure. Fiber intake was negatively associated with blood triglyceride levels (r = -0.340; p = 0.01).Conclusion: There was no association between dietary saturated fat intake and components of metabolic syndrome. There was an association between dietary fiber intake with blood triglyceride levels. Dietary fiber intake has an important role in lipid metabolism.